Preparation of ROS‐Responsive Drug‐Loaded Particles and Microneedles for Diabetic Wounds Healing - Huang, Yudi; Ni, Zhipeng; Yu, Haojie; Wang, Li; Zhang, Zhenning; Wang, Huanan; Shen, Di (Journal of applied polymer science, 2025)
ABSTRACT The treatment of diabetic wounds represents one of the most significant challenges in biomedical science, exacerbated by excessive reactive oxygen species (ROS). Traditional surgical and pharmacological interventions have become inadequate to meet therapeutic requirements. Due to the obstruction of the biofilm, the effectiveness of administration is limited by penetration. In this case, we developed a series of microneedles based on benzene boric acid‐grafted polyphosphazene, which can promote the healing of diabetic wounds. Green tea polyphenols (TP) were loaded into the above microneedles through the covalent borate bond with phenylboric acid‐based polyphosphazene (PPBA) (PPBA‐TP MNs), and TP can be released into the deeper layers of the skin in response to ROS stimulation. The matrix of PPBA‐TP MNs was sodium hyalurate (HA), which could also accelerate the healing of wounds. The wound with PPBA‐TP MNs treatment was performed on the whole layer of skin wound in the diabetic rat model. The results demonstrated that the PPBA‐TP MNs significantly enhanced wound healing.